Taxonomic Studies on Zingiberaceae of Myanmar I: A new species of Curcuma (Subgenus Ecomatae) from Myanmar - Tanaka, Nobuyuki; Aung, Mu Mu (Phytotaxa, 2019)
In the course of taxonomic studies on Zingiberaceae in Myanmar, a new species of Curcuma assignable to subgenus Ecomatae was discovered. It is described and illustrated as Curcuma kayahensis, new to science from Kayah State, southeastern Myanmar. It is morphologically most similar to C. rhomba in having the orange-red and lateral staminodes with a rhombic shape, but differs in having rhizomes yellow inside, densely pubescent lower surface of lamina, inflorescence position central, bracts light green with red veins, flowers with a longer gently curved anther.